High‐pressure phase transitions of α‐quartz under nonhydrostatic dynamic conditions: A reconnaissance study at PETRA III. (27th March 2017) - Carl, Eva‐Regine; Mansfeld, Ulrich; Liermann, Hanns‐Peter; Danilewsky, Andreas; Langenhorst, Falko; Ehm, Lars; Trullenque, Ghislain; Kenkmann, Thomas
Abstract: Hypervelocity collisions of solid bodies occur frequently in the solar system and affect rocks by shock waves and dynamic loading. A range of shock metamorphic effects and high‐pressure polymorphs in rock‐forming minerals are known from meteorites and terrestrial impact craters. Here, we investigate the formation of high‐pressure polymorphs of α‐quartz under dynamic and nonhydrostatic conditions and compare these disequilibrium states with those predicted by phase diagrams derived from static experiments under equilibrium conditions. We create highly dynamic conditions utilizing a mDAC and study the phase transformations in α‐quartz in situ by synchrotron powder X‐ray diffraction. Phase transitions of α‐quartz are studied at pressures up to 66.1 and different loading rates. At compression rates between 0.14 and 1.96 GPa s −1, experiments reveal that α‐quartz is amorphized and partially converted to stishovite between 20.7 GPa and 28.0 GPa. Therefore, coesite is not formed as would be expected from equilibrium conditions. With the increasing compression rate, a slight increase in the transition pressure occurs. The experiments show that dynamic compression causes an instantaneous formation of structures consisting only of SiO6 octahedra rather than the rearrangement of the SiO4 tetrahedra to form a coesite. Although shock compression rates are orders of magnitude faster, a similar mechanism could operate in impact events.